The Jewish-Greek tradition in antiquity and the Byzantine Empire - Aitken, J. K. (James K.); Paget, James Carleton (New York : Cambridge University Press, 2014)
"The Jewish-Greek tradition represents an arguably distinctive strand of Judaism characterized by use of the Greek language and interest in Hellenism. This volume traces the Jewish encounter with Greek culture from the earliest points of contact in antiquity to the end of the Byzantine Empire. It honors Nicholas de Lange, whose distinguished work brought recognition to an undeservedly neglected field, in part by dispelling the common belief that Jewish-Greek culture largely disappeared after 100 CE. The authors examine literature, archaeology, and biblical translations, such as the Septuagint, in order to illustrate the substantial exchange of language and ideas. The Jewish-Greek Tradition in Antiquity and the Byzantine Empire demonstrates the enduring significance of the tradition and will be an essential handbook for anyone interested in Jewish studies, biblical studies, ancient and Byzantine history, or the Greek language"--
Preface / Amos Oz -- Introduction / James K. Aitken, James Carleton Paget -- Part I. History: -- Jews and Greco-Roman culture : from Alexander to Theodosius II / Gün̈ter Stemberger -- The Jewish experience in Byzantium / Steven Bowman -- Jews and Jewish communities in the Balkans and the Aegean until the twelfth century / Alexander Panayotov -- Part II. Historiography -- Origen and the Jews: Jewish-Greek and Jewish-Christian relations / William Horbury -- Jewish-Greek studies in nineteenth- and early-twentieth-century Germany : a brief overview / Giuseppe Veltri -- Part III. Greek Bible and Language -- The origins of the Septuagint / James Carleton Paget -- The language of the Septuagint and Jewish-Greek identity / James Aitken -- Afterlives of the Septuagint : a Christian witness to the Greek Bible in Byzantine Judaism / Cameron Boyd-Taylor -- Medieval and early modern Judaeo-Greek biblical translations: a linguistic viewpoint / Julia G. Krivoruchko -- Part IV. Culture -- Philo's knowledge of Hebrew: the meaning of the etymologies / Tessa Rajak -- The plain and laughter : the hermeneutical function of the sign in Philo of Alexandria / Francis Schmidt -- Jewish archaeology and art in antiquity / David Noy -- Jewish-Greek epigraphy in antiquity / Pieter van der Horst -- The rabbis, the Greek Bible, and Hellenism / Philip Alexander -- Greek-Hebrew linguistic contacts in late antique and medieval magical texts / Gideon Bohak -- Jewish and Christian hymnody in the early Byzantine period / Wout van Bekkum -- On the Hebrew script of the Greek-Hebrew palimpsests from the Cairo Genizah / Judith Olszowy-Schlanger.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Versions; Bible; Bibel; Jews -- Civilization -- Greek influences; Jews -- Byzantine Empire -- Intellectual life; Judaism -- Byzantine Empire -- History; Hellenism; Byzantine Empire -- Ethnic relations; Juifs -- Civilisation -- Influence grecque; Juifs -- Empire byzantin -- Vie intellectuelle; Judaïsme -- Empire byzantin -- Histoire; Hellénisme.; Hellenism; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Ethnic relations; Hellenism; Jews -- Civilization -- Greek influences; Jews -- Intellectual life; Judaism; Byzantine Empire; Juden; Literatur; Kultur; Griechisch; Hebräisch; Byzantinisches Reich; Griechenland; Juden; Hellenistisch-jüdische Literatur; Griechenland; Byzantinisches Reich; Judiska intellektuella; Judendom -- historia; Hellenism; History